Gender, Religiusitas, Love of Money, dan Etika Penggelapan Pajak - Dekeny Agustina Nurachmi; Amir Hidayatulloh (Universitas Pamulang, 2021)
ABSTRACT The purpose of this research was to determine the effect of gender, religiosity, and Love of Money on tax evasion ethics. The population of this research is individual taxpayers in Daerah Istimewa Yogyakarta. The sampling technique in the research used purposive sampling, with criteria (1) individual taxpayers in Gunungkidul regency, and (2) individual taxpayers who have taxpayer-identification numbers (NPWP). The sample in this research is an individual taxpayer in Gunungkidul regency who has an NPWP. The research data collection was carried out by distributing questionnaires directly to respondents who met the criteria. Data analysis techniques in the research used multiple linear regression analysis with SPSS tools. This research obtained 80 respondents who were dominated by male respondents (41 respondents), while 39 respondents were female. This research found that the ethics of tax evasion influenced by gender and Love of Money. Meanwhile, religiosity does not affect the ethics of tax evasion.